2002
DOI: 10.1212/wnl.58.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Older people with impaired mobility have specific loci of periventricular abnormality on MRI

Abstract: These results suggest that damage to discrete frontal and occipitoparietal periventricular white matter locations may be associated with a mobility disorder of aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
90
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 20 publications
11
90
1
2
Order By: Relevance
“…Imaging studies have shown that slowing gait and parkinsonism are related to periventricular white matter changes. 33,34 Increased total and periventricular white matter hyperintensity (WMH) burden and progression of periventricular WMH burden are associated with decreased gait performance over time, whereas progression of subcortical WMH volume is associated with memory decline in cognitively intact elderly individuals. 35 In postmortem studies, motor dysfunction has been associated with the presence of neuronal loss 36 or neurofibrillary tangles in the substantia nigra 37 and amyloid plaques in the frontal lobes and basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies have shown that slowing gait and parkinsonism are related to periventricular white matter changes. 33,34 Increased total and periventricular white matter hyperintensity (WMH) burden and progression of periventricular WMH burden are associated with decreased gait performance over time, whereas progression of subcortical WMH volume is associated with memory decline in cognitively intact elderly individuals. 35 In postmortem studies, motor dysfunction has been associated with the presence of neuronal loss 36 or neurofibrillary tangles in the substantia nigra 37 and amyloid plaques in the frontal lobes and basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…WMH in these tracts can disrupt neural transmission, leading to gait slowing in older adults. 10,11,37 Tracts that traverse large areas of watershed WM are more prone to WM injury and WMH. 38 Recent evidence also suggests that inflammation influences corpus callosal changes.…”
Section: Baseline Characteristics Valuesmentioning
confidence: 99%
“…9 WMH are related to slow gait in older adults. 10,11 In regions that are free of WMH, which we refer to here as normal-appearing white matter (NAWM), subtle changes are detected on diffusion tensor imaging (DTI) as a reduction in fractional anisotropy of NAWM (NAWM-FA), denoting loss of myelin and astrogliosis at the microstructural level.…”
mentioning
confidence: 99%
“…Previous research suggests that the location or distribution of WMHs is associated with specific symptoms (Benson, et al 2002). Most previous research focused only on WMH visual inspection or volume measurement and did not distinguish anatomically distinct WMHs, while a few groups have explored semi-automated or automated methods to localize WMHs into large compartments or catergories such as periventricular white matter hyperintensities (PVWMHs) and deep white matter hyperintensities (DWMHs).…”
Section: Introductionmentioning
confidence: 99%